Macropinocytosis in phagocytes: regulation of MHC class-II-restricted antigen presentation in dendritic cells - Liu, Zhenzhen; Roche, Paul A. (Frontiers in Physiology, 2015)
Abstract Dendritic cells (DCs) are outstanding antigen presenting cells (APCs) due to their robust ability to internalize extracellular antigens using endocytic processes such as receptor-mediated endocytosis, phagocytosis, and macropinocytosis. Macropinocytosis mediates the non-specific uptake of soluble antigens and occurs in DCs constitutively. Macropinocytosis plays a key role in DC-mediated antigen presentation to T cells against pathogens and the efficiency of macropinocytosis in antigen capture is regulated during the process of DC maturation. Here, we review the methods to study macropinocytosis, describe our current knowledge of the regulatory mechanisms of antigen uptake via macropinocytosis and the intracellular trafficking route followed by macropinocytosed antigens, and discuss the significance of macropinocytosis for DC function.